Spectrophotometric determination of the total phenolic content, spectral and fluorescence study of the herbal Unani drug Gul-e-Zoofa (Nepeta bracteata Benth) - Nazish Siddiqui, Ph.D.; Abdur Rauf, M.D. (Unani); Abdul Latif, M.D. (Unani); Zeenat Mahmood, M.D. (Unani) (Journal of Taibah University Medical Sciences, 2017)
Objectives: This study quantitatively determined the total phenolic contents in ethanolic and aqueous extracts of Gul-e-Zoofa (flowers of Nepeta bracteata Benth) using a spectrophotometric method. We also performed a spectral study (UV and IR) of the ethanolic extract and a fluorescence study of the powdered drug and successive extracts to identify and characterize the genuine herbal drug, which has not been previously performed. Methods: The total phenolic content was determined quantitatively using the Folin Ciocalteu reagent, with Gallic acid as the standard. The fluorescence characteristics of the powdered drug and successive extracts with and without chemical treatment during the day and under a UV light were recorded. The UV and IR spectra of the alcoholic extract of Gul-e-Zoofa were recorded using a spectrometer. Results: The total phenolic contents of the alcoholic and aqueous extracts were found to be 326.28 and 319.14 mg/g of the Gallic acid equivalent (GAE), respectively. The wavelength of the maximum absorption in the UV spectrum was 320 nm, and the characteristic frequencies in the IR spectrum were 3465.31, 3220.07, 2927.3, 2856.1, 1709.07, 1610.19, 1404.5, 1250.2, 1056.42, 823.04, 775.58, 577.81, and 463.10 cm−1. The fluorescence characteristics of the powdered drug were also observed. Conclusion: This spectral and fluorescence study of the drug will be helpful for confirming the identity and purity of the genuine drug. The total phenolic content will be helpful for developing new drugs and standardizing the drug. The presence of a high total phenolic content shows that the flowers of N. bracteata Benth may possess antioxidant properties, which could lead to a new field of research in the future.